Underfifty Women and Breast Cancer: Narrative Markers of Meaning-Making in Traumatic Experience - Martino, Maria Luisa; Lemmo, Daniela; Gargiulo, Anna; Barberio, Daniela; Abate, Valentina; Avino, Franca; Tortoriello, Raffaele (Frontiers in Psychology, 2019)
A diagnosis of breast cancer is considered a potential traumatic event associated with physical and psychological effects. In literature, an exploration of breast cancer experience in young women is lacking, able to shed light on the narrative processes of meaning-making of the experience in specific phases of treatment, as may be the initial impact with the onset of the cancer. Meaning-making processes are determinant aspects when dealing with traumatic events. The research took place at National Cancer Institute Pascale of Naples. We collected 50 ah hoc narrative interviews to explore the different domains of the experience with under-fifty women at the first phase of the hospitalization phase. The Narrative Interviews were analyzed through a qualitative methodology constructed ad hoc. Starting from the functions of meaning-making that the narrative mediate we have highlight the different modes to articulate the narrative functions: The Organization of Temporality: chronological (38%), actualized (26%), suspended (18%), interrupted (16%), and confused (2%). The Search for Meaning: internalized (42%); generalized (24%); externalized (18%); suspended (16%). The Emotional Regulation: disconnected (44%), splitted (28%), pervasive (26%), and connected (2%). The Organization of self-other Relationship: supportive (46%), avoidant (22%), overturned (16%), and sacrificial (16%). The Finding Benefit: revaluating (38%), flattened (34%), and postponed (28%). The Orientation to Action: combative (38%), blocked (36%), and suspended (26%). Findings capture the impact with the onset of the cancer, identifying both risk and resource aspects. The study allows to identify a specific use of narrative device by under-fifty women who impacted with the experience of breast cancer. The ways in which meaning-making functions are articulated highlight the specificity of the first phase of the treatment of the cancer. From a clinical psychology point of view, our findings can be used as clinical narrative markers to grasp, in a diachronic way, the process of meaning-making, integration, and coping during the first phase of breast cancer experience in young women. We consider it valuable to increase longitudinal studies with young women to highlight trajectories of meaning-making during the different phases of the treatment to think about personalized intervention practices diachronically to the experience.